Hollow Iron Oxide Nanospheres Obtained Through a Combination of Atomic Layer Deposition and Electrospraying Technologies - Escrig-Murua, J; Patiño-Vidal, C; Vivas, L (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
In the present study, we report on the successful synthesis of hollow iron oxide nanospheres. The hollow Fe3O4 nanospheres were synthesized following a four-step procedure: electrospraying spherical PVP particles, coating these particles with alumina (Al2O3) and hematite (Fe2O3) through atomic layer deposition and, finally, a thermal reduction process to degrade the polymer (PVP) and convert hematite (Fe2O3) into magnetite (Fe3O4). A structural analysis using X-ray diffraction (XRD) confirmed the effectiveness of the thermal reduction process. A morphological analysis confirmed that the four-step procedure allowed for the obtainment of hollow iron oxide nanospheres, even though the reduction process caused a contraction in the diameter of the particles of almost 300 nm, but did not affect the thickness of the walls of the hollow spheres that remained at approximately 15 nm. Magnetic properties of the hollow iron oxide nanospheres enable their use in applications where the agglomeration of magnetic nanostructures in liquid media is commonly not allowed, such as in drug encapsulation and delivery. © 2022 by the authors.